Nanochemistry, biotechnology, nanomaterials, and their applications : selected proceedings of the 5th International Conference Nanotechnology and Nanomaterials (NANO2017), August 23-26, 2017, Chernivtsi, Ukraine /: selected proceedings of the 5th International Conference Nanotechnology and Nanomaterials (NANO2017), August 23-26, 2017, Chernivtsi, Ukraine. (2018) - Unknown
No abstract available